Sulfur Metabolism and Stress Defense Responses in Plants - Capaldi, Flávia R.; Gratão, Priscila L. [UNESP]; Reis, André R. [UNESP]; Lima, Leonardo W. [UNESP]; Azevedo, Ricardo A. (Springer Nature, 2015)
Sulfur management is an important issue in crop plant nutrition. Sulfur has a role in fundamental processes such as electron transport, structure and regulation. It is also associated with photosynthetic oxygen production, abiotic and biotic stress resistance and secondary metabolism. Sulfate uptake, reductive assimilation and integration into cysteine and methionine are the central processes that direct oxidized and reduced forms of organically bound S into their various functions. Sulfur-containing defense compounds that are crucial for plant survival during biotic and abiotic stress include elemental sulfur, hydrogen sulfide, glutathione, phytochelatins, S-rich proteins and various secondary metabolites. Formation of these compounds in plants is closely related to the supply, demand, uptake and assimilation of S. This review will highlight the role of S during the stress response in plants and the relationship between S metabolism and primary S nutrition.
Keywords: Abiotic stress; Antioxidants; Oxidative stress; Plant nutrition; Sulfur uptake and metabolism